(untitled) (Journal of the College of Basic Education, 2022)
The research aims to" reveal the effect of the Back in the back strategy on the artistic expression of second graders in the Department of Art Education- College of Fine Arts-University of Baghdad in the subject of planning and colors." To achieve this goal, the researcher has set the following two sub-goals "Preparing various technical topics within the approach used in the material planning and colors", "Measuring the impact of the Back in the back strategy on artistic expression through its application to an experimental sample from the second grade students in the Department of Art Education."the research community consisted of the second grade students-Department of Art Education,who are (157) male and female students divided into (6) classrooms, and the researcher relied on the experimental approach, and the researcher designed (3) teaching plans according to the Back in the back strategy in line with the subject Planning and colors, designing a cognitive achievement test, and building a form to evaluate students’ skill performance. Statistical methods were used (T-test equation for two independent samples, difficulty coefficient equation, discrimination factor, Kudor Richardson equation-20,C The percentage equation, ETA squared),The results of the research are: The experimental group outperforms the requirements of planning and coloring material over their peers from the control group, which came to the effectiveness of the strategy used in teaching and the size of its effect in developing students’ cognitive and performance skills. The researcher also reached the following conclusions: -The teaching plans designed according to the Back in the back strategy contributed to the students (experimental) process of the subjects that were taught according to these plans for the topic of planning and colors, making it a purposeful, self-directed and collective process. -The educational content of the teaching plans was characterized by the simplification of the learning process according to the cognitive and performance skills specified in the planning and coloring material, which contributed to advancing the competencies of the performance of the experimental group students in the implementation of the material requirements.